PENGARUH AKUNTANSI PERTANGGUNGJAWABAN, KOMITMEN ORGANISASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA MANAJERIAL PADA PT PLN (PERSERO) UNIT PELAKSANA PEMBANGKITAN TIMOR - Oscar Lete; Maria E. D. Tunti; Juendiny Chrisna Ekasari Tualaka (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to examine the effect of responsibility accounting, organizational commitment, and internal control systems on managerial performance at PT PLN (Persero) Timor Power Generation Unit (UPK Timor). The study employed a quantitative approach, with data collected through questionnaires distributed to 52 respondents. Data were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that responsibility accounting, organizational commitment, and internal control systems each have a positive and significant effect on managerial performance. Simultaneously, these three variables also have a positive and significant effect on managerial performance. The Adjusted R Square value of 0.803 indicates that 80.3% of the variation in managerial performance is explained by responsibility accounting, organizational commitment, and internal control systems, while the remaining 19.7% is explained by other factors outside the research model. These findings suggest that the effective implementation of responsibility accounting, strong organizational commitment, and effective internal control systems play an important role in improving managerial performance.